Ten years after the release of the first issue of Acta medico-biotechnica / 10 let po izidu prve številke revije Acta medico-biotechnica - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Dear readers, We almost overlooked this date – the 10th anniversary of the publication of the first issue. We are so used to its half-yearly publication that we simply forgot to count. But the fact is that on December 03, 2008 the first issue of Acta medico-biotechnica was published. Slowly we have taken it as our own, it has become a part of us. The majority of you are naming it just Acta. We have stopped thinking about whether the next issue number will be released or not. In between there were years that we survived with more difficulty, there were even doubts about it continuing, but we have endured and succeeded so that we can now light 10 candles on the cake. Of course, we will, upon this jubilee, also blow them out and at that express wishes to the journal for many further successful years.